Vermicompost quality and earthworm reproduction in different organic waste substrates - Saeed Mohammad Alipour; Ebrahim Fataei; Fatemeh Nasehi; Ali Akbar Imani (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The present study aims to evaluate the changes in parameters affecting the quality of vermicompost produced by the earthworm 'Eisenia fetida' on different organic waste substrates using multivariate analysis, variance analysis, factor analysis and principal component analysis (PCA).Method A completely randomized design experiment was conducted with a 2 × 8 factorial arrangement of experimental and control treatments in triplicate per treatment. We investigated the growth and reproduction of earthworms and the characteristics of vermicompost produced on different organic wastes and residues represented by carrot pulp (C), potato peel (P), vegetables (V) and sawdust (S) blended with cattle manure (as the main substrate) at two levels of 100 and 150 grams of each treatment in two kilograms of manure. Chemical parameters include pH, electrical conductivity (EC), carbon/nitrogen ratio (C/N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), iron (Fe) and copper (Cu) were measured in the vermicompost produced.Results The results of cluster analysis and PCA grouped nine substrate combinations into three categories with similar qualitative characteristics. The first two principal components in PCA revealed that the major parameters responsible for the qualitative changes in the produced vermicompost were iron, copper, calcium, magnesium, potassium, phosphorus and nitrogen.Conclusion Current results suggested that the treatment CPVS and the treatment S (sawdust) provided the optimal conditions for the growth and reproduction of earthworms and the production of high-quality vermicompost.